Well-design and synthesis of a water- and heat-resistant UiO-67@CNTs composite for Congo red efficient capture. (16th February 2022) - Jin, Yuning; Wu, Danping; Ma, Na; Dai, Wei
Abstract: MOFs (metal-organic frameworks) significantly suffer from water- and heat instable issues, restricting their practical application, such as the capture of hazardous anionic dyes (e.g. Congo red, CR) from water. In the present contribution, a series of novel composites (UiO-67@CNTs) composed of microporous UiO-67 (Zr6O4(OH)4(CO2)12) and mesoporous CNTs (carbon nanotubes) have been innovatively synthesized by an in-situ hydrothermal reaction strategy. This UiO-67@CNT impressively retains structural integrity whether contacted with strong acid, distilled water, and strong alkali conditions even for 20 days. Due to the existence of CNT, its heat stability can reach up to 480 °C, which is superior to that of UiO-67. Open Zr(IV) sites, mesoporous, and high surface area in the structure of UiO-67@CNTs play associative effects for CR capture ability. CR uptakes over (5.0)UiO-67@CNTs can reach 1024 mg/g, exceeding some other previous adsorbents in literature. Importantly, UiO-67@CNTs could retain a remarkable CR capture ability even after the fifth cycle. This work expands views for water-heat resistant MOF-based composite with excellent ability of CR capture. HIGHLIGHTS: UiO-67@CNTs exhibited outstanding hydrolytic stability, retaining intactness for 20 days even in strong acid and alkali. UiO-67@CNTs performed more excellent thermal stability until 480 °C. Novel UiO-67@CNTs have potential applications for CR capture. Graphical Abstract